The Efficiency of Game-Based Learning Towards Student’s Focus And Enjoyment Using Board Game: A Case Study at SK Martin - Nur Shaheerah, Mohamed Nor; Jonathan, Sidi; Andalina Dayang, Madang; Suhaira, Suhaimi; Ainin Sofea, Azhari; Nur Fatin Fareeda, Roslan; Siti Khadijah, Abdullah; Rapheal, Andar (UNIMAS Publisher, 2019)
The purpose of this game research is to observe and evaluate how the implementation of the game-based learning (embedded with IT ) can improve students’ focus in class and at the same time having fun with their study. Based on the result, students enjoy more when playing the games while studying. They tend to focus more and learn from their mistakes.